Effect of Shubishu biocolloids combined with compound Huangbai Solution lotion in the treatment of diabetic foot ulcer (术毕舒生物胶体液联合复方黄柏液涂剂治疗糖尿病足溃疡效果观察) - GAN Lu (甘露); XIE Wei (谢薇); JIANG Yonghong (江永红); ZHANG Youqiong (张友琼); YUAN Dan (袁丹); CHEN Yuanyuan (陈媛媛); MO Mei (莫梅); GONG Xuelei (龚雪蕾) (Journal of International Translational Medicine Limited, 2021)
Objective To observer the effect of Shubishu biocolloids combined with compound Huangbai Solution lotion in the treatment of diabetic foot ulcer, and evaluate its efficacy and safety. Methods A Total of 24 patients with refractory diabetic foot ulcer were divided into the observation group and control group, with 12 cases in each group. All patients received routine treatment, and those in the observation group were given external application of Shubishu biocolloids combined with compound Huangbai Solution lotion. The wound healing condition, degree of pruritus, pain, granulation tissue at wound surface area and wound infection condition were assessed at 8 weeks after intervention. Results The overall response rate was 91. 67%(11/12)in the observation group, which was higher than 58. 33%(7/12)in the control group(P＜0. 05). The scores of assessment on pruritus, pain, granulation tissue decreased in both two group at 8 weeks after intervention(P＜0. 05), and scores of pruritus, pain, granulation tissue assessment in the observation group were lower than those in the control group (P＜0. 05). There were 2 cases of wound infection reported in the control group. Conclusion The Shubishu biocolloids combined with compound Huangbai Solution lotion is effective and safe to improve the efficacy of treatment for diabetic foot ulcer, relieve general symptoms, reduce ulcer area. (目的 观察术毕舒生物胶体液联合复方黄柏液涂剂治疗糖尿病足溃疡的临床效果, 评价其有效性和安全性。方法 选择2019年4月-2020年4月在贵州中医药大学第一附属医院就诊的难愈性糖尿病足溃疡患者24例, 分为观察组和对照组, 每组12例。2组均给予常规对症治疗, 观察组患者在常规治疗后给予术毕舒联合复方黄柏液涂剂。换药并观察记录8周后2组创面愈合率、创面瘙痒、疼痛、肉芽形态评分和创面感染情况。结果 观察组总有效率为91. 67%(11/12), 高于对照组的58. 33%(7/12), 差异有统计学意义(P＜0. 05)。与治疗前比较, 2组治疗后8周创面瘙痒评分、疼痛及肉芽形态评分均降低(P＜0. 05), 且观察组创面瘙痒评分、疼痛及肉芽形态评分较对照组降低, 差异有统计学意义(P＜0. 05)。对照组发生感染2例, 观察组无患者发生感染。结论 术毕舒生物胶体液联合复方黄柏液涂剂能进一步提高糖尿病足溃疡的治愈率, 改善全身症状, 缩小溃疡面积, 并且安全有效。)